ORGANIZATION COMMITMENT AND ENVIRONMENTAL UNCERTAINTY MODERATING BUDGET PARTICIPATION ON BUDGETARY SLACK - Huseno, Tun (Jurnal Aplikasi Manajemen, 2017)
This research was conducted in order to determine the effect of budget participation, the budgetary slack, knowing the influence of organizational commitment moderates the effect of budget participation on budgetary slack, knowing the effect of moderating influence of environmental uncertainty budget participation on budgetary slack on the Government of West Sumatra Province. The sample in this study was 105 respondents and was taken by purposive sampling. The data used in this study are primary data, collected by surveying techniques by distributing questionnaires to each echelon III and IV in OPD Government of West Sumatra Province. The analysis technique used is the analysis of partial least square (PLS) based variance.The result of hypothesis analysis showed that budget participation and significant negative effect on the budgetary slack. Organizational commitment positively and significantly as a moderating budget participation on budgetary slack. Environmental uncertainties and significant negative effect as moderating budget participation on budgetary slack